Synthesis and reactivity of selenium functionalised allylidynes and propargylidynes. Issue 41 (1st October 2018) - Hill, Anthony F.; Manzano, Richard A.; Ward, Jas S.
Abstract : The reactions of the trimethylsilylpropargylidyne [W(}CC}CSiMe3 )(CO)2 (Tp*)] (1 : Tp* = hydrotris(dimethylpyrazolyl)borate) towards selenium centred reagents when treated with tetrabutylammonium fluoride (TBAF) were explored in order to prepare alkynylselenolato propargylidynes, e.g., [W(}CC}CSePh)(CO)2 (Tp*)]. Abstract : The reactions of the trimethylsilylpropargylidyne [W(}CC}CSiMe3 )(CO)2 (Tp*)] (1 : Tp* = hydrotris(dimethylpyrazolyl)borate) towards selenium centred reagents when treated with tetrabutylammonium fluoride (TBAF) were explored in order to prepare alkynylselenolato propargylidynes, e.g., [W(}CC}CSePh)(CO)2 (Tp*)]. Treating1 with TBAF and PhSeSePh resulted in E and Z isomers of the vinylcarbyne (allylidyne) complex [W}CC(SePh){CHSePh(CO)2 (Tp*)] in addition to traces of the trisubstituted derivative [W}CC(SePh){C(SePh)2 (CO)2 (Tp*)]. Reactions with PhSeCl resulted in the isolation of bimetallic bis-substituted allylidyne complex [(Tp*)(CO)2 W}CC(SePh){C(SePh)C}CC}W(CO)2 (CO)2 (Tp*)] as well as the desired selenolatopropargylidyne [W(}CC}CSePh)(CO)2 (Tp*)].